1998
DOI: 10.1017/s0265021598000131
|View full text |Cite
|
Sign up to set email alerts
|

International, multicentre, placebo-controlled study to evaluate the effectiveness of ondansetron vs. metoclopramide in the prevention of post-operative nausea and vomiting

Abstract: Ondansetron 4 mg was compared with metoclopramide 10 mg for prevention of post-operative nausea and emesis in in-patients undergoing major gynaecological surgery in this double-blind, randomized, placebo-controlled, multicentre study. A total of 1044 patients received a single intravenous (i.v.) injection of study medication immediately before induction of anaesthesia. Nausea and emesis were assessed over the 24 h post-operative period. Significantly more patients who received ondansetron experienced no emetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…As mentioned above, the anaesthetists involved in the care of these patients were unaware of the study and therefore continued their regular practice of antiemetic prescription. Some studies [4] have shown no difference in PONV with perioperative prochlorperazine versus placebo (13% and 14%, respectively) whereas others show a benefit with perioperative antiemetic [3]. It has been suggested that those subsets of patients at high risk of PONV such as women undergoing gynaecological surgery should be given a prophylactic antiemetic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the anaesthetists involved in the care of these patients were unaware of the study and therefore continued their regular practice of antiemetic prescription. Some studies [4] have shown no difference in PONV with perioperative prochlorperazine versus placebo (13% and 14%, respectively) whereas others show a benefit with perioperative antiemetic [3]. It has been suggested that those subsets of patients at high risk of PONV such as women undergoing gynaecological surgery should be given a prophylactic antiemetic.…”
Section: Discussionmentioning
confidence: 99%
“…Its overall incidence is 15-35% [1][2][3] and varies according to patient, anaesthetic and surgical factors. Most studies on PONV in women are based on gynaecological surgery which is known to be associated with a high incidence of PONV of up to 81% [4,5]. It has been noted on routine postoperative pain assessment ward rounds in this hospital that many women following breast surgery complain of nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…The data referring to the effectiveness of ondansetron in the two sub-groups of patients (with respect to the PH-PONV) were obtained directly from the original in 8 studies (8,9,15,17,(23)(24)(25)27), and in the rest of the studies from correspondence with the authors or study sponsors.…”
Section: Resultsmentioning
confidence: 99%
“…Prophylactic ondansetron administered i.v or orally has been evaluated in the prevention of PONV [22][23][24][25][26][27][28][29][30][31][32]. In a randomized, double-blind, placebo-controlled trial, ondansetron 4-8 mg administered i.v.…”
Section: Serotonin Receptor Antagonistsmentioning
confidence: 99%
“…immediately after induction of anesthesia, in the prevention of PONV [28]. Similarly, Morris et al [29] and Krobbuaban et al [30] compared the efficacy of ondansetron 4 mg and metoclopramide 10 mg, administered i.v. immdeiately before induction of anesthesia.…”
Section: Yoshitaka Fujiimentioning
confidence: 99%